2017
DOI: 10.1186/s13036-017-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of poly(γ-glutamic acid) production via online determination of viscosity and oxygen transfer rate in shake flasks

Abstract: BackgroundPoly(γ-glutamic acid) (γ-PGA) is a biopolymer with many useful properties making it applicable for instance in food and skin care industries, in wastewater treatment, in biodegradable plastics or in the pharmaceutical industry. γ-PGA is usually produced microbially by different Bacillus spp. The produced γ-PGA increases the viscosity of the fermentation broth. In case of shake flask fermentations, this results in an increase of the volumetric power input. The power input in shake flasks can be determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
(60 reference statements)
4
5
0
Order By: Relevance
“…Because ammonium was used as nitrogen source, γ‐PGA is produced during microbial growth in phase I (Meissner et al, ). In the second phase (II: 18.5–32 hr), the produced γ‐PGA is degraded (Meissner et al, ; Regestein née Meissner et al, ; Wilming et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Because ammonium was used as nitrogen source, γ‐PGA is produced during microbial growth in phase I (Meissner et al, ). In the second phase (II: 18.5–32 hr), the produced γ‐PGA is degraded (Meissner et al, ; Regestein née Meissner et al, ; Wilming et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It evaluates the shift in the angular position of the bulk liquid relative to the direction of the centrifugal acceleration. The measurement system is different from the previously used, based on power input measurement (Regestein Née Meissner et al, 2017).…”
Section: Cultivation For On-line Monitoring (Otr and Viscosity Measurmentioning
confidence: 99%
“…Growth was closely monitored by measuring the OTR. Regestein et al have shown that the γ-PGA concentration is closely related to viscosity (Regestein Née Meissner et al, 2017).…”
Section: γ-Pga Production Under Varying Substrate Concentrationsmentioning
confidence: 99%
“…Probably the mucilage, which already has a fairly high viscosity, may not increase its viscosity even if the c-PGA content is increased. In addition, Regestein Nee Meissner et al reported that even though the amount of c-PGA is important in the viscosity of mucilage, the influence of Mw of c-PGA is greater (Regestein Nee Meissner et al, 2017). By the way, it is known that the Mw of c-PGA can be greatly reduced as the fermentation progresses, thereby reducing viscosities (Feng et al, 2017).…”
Section: Effect Of Added Nitrogen Sourcesmentioning
confidence: 99%